1980
DOI: 10.1021/es60170a009
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffractometry examination of air filters for compounds emitted by lead smelting operations

Abstract: X-ray diffractometry has been used to characterize particulate pollutant fallout from smelting operations in Missouri. An identification technique has been developed that needs only 1-15 mg of collected material from a Hi-Vol filter. Compound identification reveals changes in the toxic lead compounds after corrective action was taken in the manufacturing process. Typical diffraction patterns are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 3 publications
(4 reference statements)
2
13
1
Order By: Relevance
“…Currently, there is considerable interest in the various compounds that feature in aerosol exposure during the production and use of metals and in Our results of smelter lead dust speciation analysis for both the bulk dust samples and airborne dust samples confirmed that the lead dust mineralogy varies widely throughout the smelter, consisting of remnant sulfides and multimetal oxide phases. These findings are consistent with other studies that have reported galena as the major constituent in samples associated with ore handling, whereas lead oxide species (PBOX, PbO.PbSO4) were the dominant species associated with smelter operations (9). Changes to the ore during the smelting process result in changes to the mineralogy of the airborne dust, which are reflected in the Tessier sequential extraction method.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, there is considerable interest in the various compounds that feature in aerosol exposure during the production and use of metals and in Our results of smelter lead dust speciation analysis for both the bulk dust samples and airborne dust samples confirmed that the lead dust mineralogy varies widely throughout the smelter, consisting of remnant sulfides and multimetal oxide phases. These findings are consistent with other studies that have reported galena as the major constituent in samples associated with ore handling, whereas lead oxide species (PBOX, PbO.PbSO4) were the dominant species associated with smelter operations (9). Changes to the ore during the smelting process result in changes to the mineralogy of the airborne dust, which are reflected in the Tessier sequential extraction method.…”
Section: Discussionsupporting
confidence: 91%
“…1,[16][17][18][19][20][21][22] Its apparent absence may be due to a number of factors, such as the sampling location, sinter chemistry and conditions, reaction kinetics, or possibly retention in the sinter. The presence of Clbearing phases in the Pb smelting literature is relatively uncommon, with only Pb 2 OCl 2 being reported.…”
Section: Discussionmentioning
confidence: 99%
“…The main Pb species emitted from Pb smelters are: PbS0 4 and PbO.PbS0 4 (Pacyna et al, 1991;O'Neill et al, 1982;Eatough et al, 1979;Corrin and Natusch, 1979;Harrison and Williams, 1983;Foster and Lott, 1980). These compounds are thought to form in the stack from lead fume, S0 2 and hot air (Biggins and Harrison, 1979).…”
Section: Chemical Formmentioning
confidence: 99%